Target indicators and mechanistic function of epidrugs with activity against multiple stages of Plasmodium falciparum parasites - Birkholtz, Lyn-Marie (University of Pretoria, 2022)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2021.